2014
DOI: 10.1111/dewb.12068
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Host Country Ethical Oversight of International Research: The Use of a Collaborative ‘Pre‐Review’ Mechanism for a Study of Fexinidazole for Human African Trypanosomiasis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Budgetary constraints, lack of training, expertise and lack of full time administrators have also been highlighted as major challenges to African RECs [7][8][9][10][11][12][13]. The findings of this survey revealed that the use of modern review technologies, can positively address the communication, storage, security and confidentiality issues as well as, cushion the RECs limited budgets by reducing their operational costs such as telephone, photocopying and protocol distribution costs.…”
Section: Discussionmentioning
confidence: 99%
“…Budgetary constraints, lack of training, expertise and lack of full time administrators have also been highlighted as major challenges to African RECs [7][8][9][10][11][12][13]. The findings of this survey revealed that the use of modern review technologies, can positively address the communication, storage, security and confidentiality issues as well as, cushion the RECs limited budgets by reducing their operational costs such as telephone, photocopying and protocol distribution costs.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment algorithm for inclusion of WoSuPs in various phases of drug development is described in Fig 1. To facilitate the analysis, it is recommended that a collaborative "prereview" of the ethical oversight is set-up, conducted by an ad hoc ethics committee including representatives from the target country or countries and from mature countries, in collaboration with internationally recognized scientific experts [41].…”
Section: First and Foremost Dndi Recommends Evaluating The Implicatimentioning
confidence: 99%
“…While double or multiple reviews of international research protocols are common, we are not aware of any successful mechanisms for joint ethics review (Meslin et al , 2014; Tierney et al , 2013), with a single reported exception from the field of human African trypanosomiasis. A ‘pre-review’ process of the protocols for DNDi and partners’ pivotal Phase II/III fexinidazole study brought together in 2012 the Ethics unit of WHO and representatives of ECs from six African countries with the aim of reducing duplication of efforts (Coleman et al , 2015). This model of joint ‘pre-review’ of the ethical challenges foreseeable within a whole research plan, may be feasible for a public health emergency, if representatives of relevant organizations are pre-identified, available to meet on short notice, the resultant consensus review is agreed in advance to be acceptable to all and some organization takes on the role of coordination and engagement with the researchers.…”
Section: Procedural Issues Faced By the Msf Erb During The West Africmentioning
confidence: 99%